Distribution characteristics, risk assessment, and source analysis of heavy metals in typical lake sediments in Inner Mongolia, China - Zhang, Hui; Zhao, Shengnan; Shi, Xiaohong; Sun, Biao; Cui, Zhimou; Zhao, Yunxi; Zhang, Jinda (Ecological indicators, 2024)
•Cd element is the main pollutant in sediment of lakes in Inner Mongolia.•Quantitative analysis of heavy metal sources using models.•Frequent human activities in the central region have led to severe lake pollution.•Massive collection of sediment samples from numerous lakes in Inner Mongolia for determination. As an important indicator of water pollution, heavy metals in lake sediments can reflect the severity of pollution in the entire study area. Although the risk assessment of heavy metals in sediment from various lakes has been widely studied, there is a lack of understanding on the overall pollution risk assessment of heavy metals in sediment from Inner Mongolia lakes located in cold and arid regions. This study based on data from 2019 to 2023 on heavy metals (Cu, Zn, Pb, Cr, and Cd) in typical lake sediments in Inner Mongolia, combining toxicity, ground accumulation index, and potential ecological risks with Monte Carlo simulation to evaluate lakes. Furthermore, the origins of heavy metals in lake sediments were quantitatively analyzed using a qualitative analysis and an absolute principal component core–multiple linear regression model. This study presented the following results. Firstly, according to the toxicity index, ground accumulation index, and potential ecological risk coefficient, Cd and Cr were identified as the most hazardous and toxic elements in typical lake sediments in Inner Mongolia. Secondly, the degree of lake pollution in Inner Mongolia followed a heavy to light gradient, with central > eastern > western. The pollution in western lakes primarily originated from natural factors, whereas central lakes were mainly affected by pollutants from industry, agriculture, and human activities. Eastern lakes experienced pollution primarily from animal husbandry activities and natural factors. The comprehensive analysis presented in this study can serve as a valuable reference for the restoration of polluted lakes.